EFEKTIVITAS PROGRAM PEMBANGUNAN KELUARGA KEPENDUDUKAN DAN KELUARGA BERENCANA (BANGGA KENCANA) DI DPPKBP3A KABUPATEN SUMEDANG - Atujahro, Hilmi (JRPA - Journal of Regional Public Administration, 2025)
The effectiveness of the Family Development, Population Control, and Family Planning program needs to be evaluated to measure the extent of achievements in family development, population control, and family planning. This research aims to determine the extent to which the BANGGA KENCANA program implemented by the DPPKBP3A of Sumedang Regency has been carried out, particularly in supporting the improvement of family quality of life and community empowerment based on population data and family welfare. This research uses a qualitative approach. The sampling technique used is purposive sampling. The informants in this study include the Head of Advocacy, Information and Movement, the Head of Family Planning, the Financial and Program Subsection Implementer, and Family Planning Counsellors. The data collection techniques used are literature study and field study which consists of observation, interviews, documentation, and triangulation. Meanwhile, the data processing procedures in this study are data collection, data reduction, and drawing conclusions. Based on the research results then in the data analysis, it was concluded that the effectiveness of the BANGGA KENCANA program at the DPPKBP3A of Sumedang Regency has been implemented quite well, but there are some shortcomings. This can be seen from several factors such as the lack of ability of the program implementers, the understanding of the respondents, the satisfaction of the respondents and the understanding of the program content, the community has not realized the importance of the program, and budget constraints. Based on the research, there are several suggestions including strengthening human resource capacity, weather mitigation, facility improvement, and recruitment and training of cadres.